Moving Online: Taking Teaching and Learning Beyond Four Walls - Rowe, Stephen (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
In this session, Stephen Rowe shares his experiences developing an entirely online offering of an Australian undergraduate course catering to 200 students enrolled across 3 campuses. The model that was developed serves as the centre-piece and "end-point" of his PhD. Practical integration of synchronous and asynchronous elements of the online model will be described. By recording synchronous sessions, staff time normally spent on repeat sessions was freed-up and used for additional support of student learning across each week. Asynchronous elements of the model allowed students flexibility with their assessment tasks and enabled them to progress through content at their own pace. As well as describing the online model, some of the key lessons learned, student activity, results and feedback will be presented for discussion.